“Successful” Internationalization: European Insights - Rumbley, Laura E.; Hudson, Ross; Sandstrom, Anna-Malin (International Higher Education, 2019)
Data examined from “The EAIE Barometer: Signposts of Success” (2018)—specifically from among respondents who reported high levels of progress with respect to their international activities, confidence in their institution’s performance, and optimism about the future—exhibits some commonalities with respect to matters of motivation, organization, and execution. Aligning internationalization strategy with institutional mission, positioning the internationalization strategy and its supporting actors purposefully within the institution, and implementing agendas that are both expansive and meaningfully resourced seems to add up to a recipe for (self-reported) success.